(untitled) (PerCursos, 2023)
This article reflects how the COVID-19 pandemic updated stereotypes of old age and the aging process population in the world. We investigate different moments of visions construction of old age in documents produced by international bodies responsible for debating and proposing actions for the world aging collaborates with the development of societies and states. We show how, recently, there an update of the image of the elderly as a fragile, inactive and costly to the states and as such a perception does not match with the pre-pandemic efforts that celebrated aging as a victory and presented it as a challenge until we reached in the context in which it became possible to discuss the classification of old age as a disease. The methodology used includes the analysis of official documents of the United Nations (UN) and the interpretation of speeches by representatives of the Organization World Health Organization (WHO) between the months of December 2019 to March 2020. The main conclusions of this article were that verify the existing disputes in western societies about the debate about old age and aging, the presence of a prejudiced narrative (ageism) and the association of old age with the unilateral idea of vulnerability to Covid-19.